Supported material and method for catalytically oxidizing cycloalkane by using same
By loading the vanadium compound catalyst on the multi-stage pore ZSM-5 molecular sieve, the conversion rate of cyclohexanyl oxidation and KA oil selectivity are improved, and the problems of low selectivity of cyclohexyl hydrogen peroxide and many by-products are solved, and the problem of low selectivity of cyclohexyl hydrogen peroxide and many by-products are achieved. High-efficiency and low-cost cycloalkane catalytic oxidation process.
Patent Information
- Application Number
- CN202310690533.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-17
AI Technical Summary
The selectivity of the formation of cyclohexanyl hydrogen peroxide in the existing cyclohexanyl oxidation process is low, and the by-products produced by-oxidation are unfavorable for subsequent decomposition reactions, resulting in unsatisfactory yields of cyclohexanone and cyclohexanol, which increases production costs.
Using a vanadium-type supported catalyst, the vanadium compound is supported in a multi-stage pore ZSM-5 molecular sieve to catalyze cyclohexanyl oxidation, improve the cyclohexane conversion rate and the selectivity of KA oil, and reduce industrial costs.
It improves the conversion rate of cyclohexanyl oxidation and the selectivity of KA oil, reduces the generation of by-products, reduces the content of cycloalkyl hydroperoxides, improves the purity and production efficiency of the product, and reduces the environmental impact.
Smart Images

Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of supported materials and a production process for applying the materials to catalytic oxidation of cycloalkanes, and belongs to the field of fine chemicals. Background Art
[0002] The oxidation reaction of cycloalkanes mainly produces cycloalkyl ketones and cycloalkyl alcohols. They are both important raw materials in industry. For example, cyclohexanone is an important organic chemical raw material and industrial solvent, widely used in medicine, paint, coating, rubber, pesticide industry, printing and plastic recycling. At present, the main method for industrial production of cyclohexanol and cyclohexanone is cyclohexane liquid phase oxidation. This mixture produced by cyclohexane oxidation is usually called KA oil.
[0003] The traditional process of cyclohexane oxidation to produce KA oil, i.e., a mixture of cyclohexanone and cyclohexanol, is carried out in two steps. First, cyclohexane is oxidized to prepare an oxidation liquid containing cyclohexyl hydroperoxide (CyOOH). In the second step, CyOOH is decomposed to obtain KA oil. With the restrictions of regulations in various countries around the world, the demand for replacement of environmentally unfavorable catalysts such as chromium and cobalt is becoming more and more urgent. Most technologies have begun to focus on the use of different types of homogeneous catalysts to catalyze the oxidation of cyclohexane with hydrogen peroxide to prepare KA oil. Currently, most efforts are focused on the use of molecular sieves, polymers, and transition metal complexes supported by silica. Although some of these materials show relatively good activity and selectivity for K / A oil, most of them will undergo deactivation and / or metal leaching, which hinders their industrial application.
[0004] For example, patent CN111318296A discloses a method for preparing a loaded cobalt / carbon nanotube material derived from a zeolite imidazole framework material, characterized in that the loaded cobalt / carbon nanotube material is Co-Co-xO-y / CN; the method comprises the following steps: weighing a certain amount of cobalt nitrate and dissolving it in water and marking it as solution A, weighing a certain amount of dimethylimidazole and triethylamine and dissolving them in water and marking it as solution B, uniformly mixing solution A and solution B to obtain a mixed solution, stirring and centrifuging, and washing; drying the obtained precipitate to obtain a zeolite imidazole framework material; dissolving cobalt nitrate in water to prepare a precursor solution; immersing the obtained zeolite imidazole framework material in the precursor solution, stirring overnight, then drying, and calcining in a nitrogen atmosphere at a calcination temperature of 900°C to obtain Co-Co-xO-y / CN with different Co loading amounts. Under the reaction conditions: catalyst accounts for 0.6% of the reactant mass, cyclohexane is 20 mL, reaction time is 8 h, temperature is 130 ° C, oxygen pressure is 0.8 MPa, the conversion rate of cyclohexane is 12.81%, and the selectivity of KA oil is 96.3%.
[0005] Patent CN111943808A discloses a method for the synergistic catalytic oxidation of cycloalkanes by MOFs PCN-224 (Mn) / Zn (II) salts. PCN-224 (Mn) (0.001%~5%, g / mol) and Zn (II) salts (0.01%~10%, mol / mol) are dispersed in cycloalkanes, the reaction system is sealed, the temperature is raised to 120°C with stirring, oxygen is introduced to 1.0 MPa, and the reaction is stirred for 8.0 hours. The cyclohexane conversion rate is 7.00%, the cyclohexanol selectivity is 75.58%, and the cyclohexanone selectivity is 17.49%.
[0006] Although heterogeneous precious metal catalysts have good cyclohexane oxidation activity, the cost of such catalysts is high, which greatly limits their prospects for industrial application. Therefore, researchers have also prepared a variety of homogeneous catalysts. Among them, vanadium compounds can be used as a good catalyst. For example, patent CN109251126 discloses a method for cyclohexane oxidation to produce KA oil, which is catalyzed by a vanadium phosphorus oxide catalyst. The vanadium phosphorus oxide is prepared by the following method: V205, phosphoric acid and distilled water are reacted at 100~120°C for 16~24 hours. The solid product obtained is added to an isobutanol solvent and reacted at 90~130°C for 16~24 hours to obtain a catalyst precursor, which is activated to obtain the catalyst. The conversion rate of cyclohexane using a vanadium phosphorus oxide catalyst reaches 7~8%, and the selectivity of KA oil can reach about 50%. CN109251125 discloses a method for preparing cyclohexanol by oxidation of cyclohexane, wherein the reaction is catalyzed by a vanadium phosphorus oxygen catalyst, and the catalyst is prepared by the following method: V205 and phosphoric acid are reacted in an aqueous solution environment, and the obtained powder product is added to isobutanol, and the reaction is carried out at 30-90°C for 4-8 hours under normal pressure, and the solvent is evaporated to dryness, and the solid is dried to obtain a catalyst powder; or the catalyst is made into a supported type. The present invention uses a vanadium compound to be supported on a molecular sieve, and applies it to the oxidation of cyclohexane to prepare KA oil, thereby providing a new method for catalytic oxidation of cyclohexane to prepare KA oil. By using the method of the present invention, the conversion rate of cyclohexane and the selectivity of KA oil are improved; high-purity KA oil is obtained, and the industrial cost is reduced. This also shows that vanadium supported catalysts can be used for catalytic oxidation of cycloalkanes. Summary of the invention
[0007] At present, one of the main industrial preparation methods of cyclohexanone is the cyclohexane oxidation process. The non-catalytic oxidation process is commonly used in industry, which has the disadvantages of low selectivity for generating cyclohexyl hydroperoxide, and organic acids such as adipic acid, glutaric acid, and succinic acid produced by excessive oxidation have an adverse effect on the catalyst activity of the subsequent decomposition reaction, resulting in unsatisfactory molecular yields of cyclohexanone and cyclohexanol generated by the decomposition reaction of cyclohexyl hydroperoxide, low ketone-alcohol yields, and increased production costs. Solution
[0008] In order to better solve the shortcomings of cyclohexane oxidation technology, reduce the proportion of cyclohexane oxidation by-products, and increase the yield of cyclohexane oxidation products, the applicant has conducted in-depth research and invented a new technology for catalytic oxidation containing a vanadium-based supported catalyst, which can be used for the catalytic oxidation process of cyclohexane oxidation.
[0009] That is, a method for preparing a mixture of alkyl alcohols and alkyl ketones from cycloalkane catalyzed by a vanadium-based supported catalyst, wherein the conversion rate of cycloalkane is not less than 16%, and the selectivity of ketone / alcohol is not less than 95%. The method comprises oxidizing cycloalkane in a heterogeneous phase, catalyzed by the vanadium-based supported catalyst.
[0010] Wherein, the vanadium compound of the vanadium supported catalyst comprises at least one compound selected from the following structures: .
[0011] In the present invention, the pore size of the supported multi-level pore ZSM-5 molecular sieve is 2-20 nm; the loading amount of the vanadium compound in the supported material is 0.3-30%.
[0012] In the present invention, the preferred supported multi-level pore ZSM-5 molecular sieve has a pore size of 2 to 10 nm; and the loading amount of the vanadium compound in the supported material is 0.5 to 25%.
[0013] In the present invention, the particle size of the supported multi-level pore ZSM-5 molecular sieve is 100-500 nm, and the specific surface area is 300-800 m 2 / g, the silicon-aluminum atomic ratio is 20-500.
[0014] In the present invention, the preferred supported multi-level pore ZSM-5 molecular sieve has a particle size of 100 to 300 nm and a specific surface area of 300 to 600 m 2 / g, the silicon-aluminum atomic ratio is 50-400.
[0015] In the present invention, the preparation method of the carrier at least comprises: preparing a dry gel from raw materials of silicon material, aluminum material, template agent and alcohol compound; and crystallizing the dry gel in an atmosphere containing water vapor under closed conditions to obtain a multi-level pore ZSM-5 molecular sieve.
[0016] In the present invention, the silicon material: aluminum material: template agent: alcohol compound = 1.01-1.15: 0.001-0.2: 0.01-0.2: 5-1000.
[0017] In the present invention, the preferred ratio of silicon material: aluminum material: template agent: alcohol compound is 1.01-1.1: 0.001-0.1: 0.01-0.1: 50-800.
[0018] In the present invention, the mixed raw gel is dried at 10-50° C. for not less than 24 hours to obtain the dry gel.
[0019] In the present invention, the crystallization time is 24 to 120 hours, and the crystallization temperature is 100° C. to 250° C.
[0020] In the present invention, the preferred crystallization time is 48 to 120 hours, and the crystallization temperature is 120° C. to 200° C.
[0021] In the present invention, the preparation method of the supported vanadium compound at least comprises: adding a carrier into a solution containing a vanadium compound, impregnating, drying, and calcining to obtain the supported material.
[0022] In the present invention, the solid-liquid ratio of the impregnation is 1:2-15.
[0023] In the present invention, the preferred solid-liquid ratio of the impregnation is 1:5-10.
[0024] In the present invention, the conditions for the immersion include: the stirring time is 8 to 24 hours.
[0025] In the present invention, the preferred conditions for impregnation include: stirring time of 12 to 24 hours.
[0026] In the present invention, the calcination conditions include: a calcination temperature of 200 to 800° C. and a calcination time of 1 to 8 hours.
[0027] In the present invention, the preferred calcination conditions include: a calcination temperature of 400 to 700° C. and a calcination time of 2 to 6 hours.
[0028] In the present invention, the cycloalkane is a cycloalkane containing three or more carbon atoms, and also includes a cycloalkane containing an alkyl substituent.
[0029] In the present invention, the preferred cycloalkane is one of cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane and cyclododecane.
[0030] In the present invention, the amount of the catalyst is 0.01% to 5% by weight based on the total weight of the reaction mixture.
[0031] In the present invention, the preferred amount of the catalyst is 0.01% to 0.1% by weight based on the total weight of the reaction mixture.
[0032] In the present invention, the reaction pressure is 0.10-5 MPa.
[0033] In the present invention, the reaction pressure is preferably 0.10 to 2 MPa.
[0034] In the present invention, the stirring rate is 100-1200 rpm.
[0035] In the present invention, the stirring rate is preferably 300-1000 rpm.
[0036] In the present invention, the oxidant is oxygen, air or any mixture thereof.
[0037] In the present invention, the oxidant is not particularly limited, and for example, sulfoxides such as air, oxygen, dimethyl sulfoxide, dibutyl sulfoxide, diphenyl sulfoxide, and tetramethylene sulfoxide can be used. Two or more of these oxidants can be mixed. From the viewpoint of productivity and ease of operation, it is preferred to use air, oxygen, dimethyl sulfoxide, tetramethylene sulfoxide, or a mixture of these oxidants.
[0038] In the present invention, preferred oxidants are oxygen and air.
[0039] In the present invention, when oxygen is used as an oxidant, oxygen can also be mixed with other gases for use, for example, oxygen can be mixed with air or an inert gas (hydrogen, hydrogen, etc.) for use.
[0040] In the present invention, when air or oxygen is used as an oxidant, there is no particular limitation on the method of supplying air or oxygen. For example, the following methods can be used: a method of replacing the gas phase in contact with the reaction solution with air or oxygen, a method of allowing the gas phase in contact with the reaction solution to flow in air or oxygen, a method of blowing air or oxygen into the reaction solution, etc.
[0041] In the present invention, the reaction time can be determined according to the reactants, and the reaction time is usually 1 to 600 minutes; the preferred reaction time is 30 to 240 minutes.
[0042] In the present invention, the reaction time can be determined according to the reactants, and the reaction temperature is usually 0°C to 200°C; the preferred reaction temperature is 60°C to 180°C.
[0043] Beneficial effects: The present invention has the advantages of simple catalyst preparation, high conversion rate of catalytic oxidation of cycloalkanes, high ketone / alcohol yield, low reaction temperature, few by-products, and small environmental impact. In addition, the present invention has low cycloalkyl hydroperoxide content and high safety factor. The present invention provides an efficient, feasible and safe method for selective catalytic oxidation of cycloalkanes to synthesize cycloalkyl alcohols and cycloalkyl ketones. Implementation
[0044] The technical scheme of the present invention is further described below in conjunction with the examples. The following examples will further illustrate the present invention, but are not intended to limit the content of the present invention. All reagents used in the examples are commercially available chemically pure reagents.
[0045] Example 1 0.10 g of aluminum isopropoxide, 15 mL of ethyl orthosilicate, 10 g of tetramethylammonium hydroxide, 1.5 mL of hexadecyltrimethoxysilane and 50 mL of ethanol were added to a container in sequence, stirred at room temperature to form a gel, and after drying at room temperature for 48 h, transferred to a 250 mL stainless steel hydrothermal autoclave lined with polytetrafluoroethylene, and crystallized at 180 ° C for 48 h; after filtering, washing, and drying at 120 ° C for 3 h, a multi-level pore ZSM-5 molecular sieve A was obtained.
[0046] Example 2 0.10 g of aluminum isopropoxide, 20 mL of ethyl orthosilicate, 12 g of tetramethylammonium hydroxide, 1.6 mL of hexadecyltrimethoxysilane and 50 mL of ethanol were added to a container in sequence, stirred at room temperature to form a gel, and after drying at room temperature for 48 h, transferred to a 250 mL stainless steel hydrothermal autoclave lined with polytetrafluoroethylene, and crystallized at 180 ° C for 72 h; after filtering, washing, and drying at 120 ° C for 3 h, a multi-level pore ZSM-5 molecular sieve B was obtained.
[0047] Example 3 The obtained molecular sieves A and B were ground, tableted, crushed, and sieved, and particles with a size of 20 to 40 mesh were taken as carrier samples.
[0048] Example 4 The carrier A was added into a solution containing 0.02% of vanadium compound a, fully stirred and impregnated for 12 hours, dried at 80° C. for 3 hours, and calcined at 600° C. for 4 hours to obtain the supported material M.
[0049] Example 5 The carrier B was added into a solution containing 0.05% of the vanadium compound b, and the solution was fully stirred and impregnated for 12 hours. After drying at 80° C. for 3 hours, the solution was calcined at 700° C. for 6 hours to obtain the supported material N.
[0050] Example 6 In a 100 ml polytetrafluoroethylene-lined autoclave, 20 g of cyclohexane and 0.02% of the supported material M of Example 4 were added, the temperature was raised to 100° C. with stirring, oxygen was introduced at 0.2 MPa, and the reaction was stirred at 500 rpm for 2 hours. After the reaction was completed, 2 g of triphenylphosphine was added to the reaction mixture, stirred at room temperature for 1 hour, and a sample was taken for gas chromatography analysis. The cyclohexane conversion rate was 19.6%, and the ketone / alcohol selectivity was 96.5%.
[0051] Example 7 In a 100 mL polytetrafluoroethylene-lined autoclave, 42 g of cyclopentane and 0.01% of the supported material N of Example 5 were added, the temperature was raised to 120°C with stirring, and air was introduced at 1.15 MPa, and the reaction was stirred at 600 rpm for 2 hours. After the reaction was completed, 4 g of triphenylphosphine was added to the reaction mixture, stirred at room temperature for 1 hour, and a sample was taken for gas chromatography analysis. The cyclopentane conversion rate was 24.2%, and the ketone / alcohol selectivity was 96.7%.
[0052] Example 8 In a 100 mL polytetrafluoroethylene-lined autoclave, 42 g of cycloheptane and 0.02% of the supported material N of Example 5 were added, the temperature was raised to 120°C with stirring, and air was introduced at 1.15 MPa, and the reaction was stirred at 600 rpm for 2 hours. After the reaction was completed, 4 g of triphenylphosphine was added to the reaction mixture, stirred at room temperature for 1 hour, and a sample was taken for gas chromatography analysis. The cycloheptane conversion rate was 27.1%, and the ketone / alcohol selectivity was 94.7%.
[0053] Example 9 In a 100 ml polytetrafluoroethylene-lined autoclave, 10 g of cyclononane and 0.02% of the supported material M of Example 4 were added, the temperature was raised to 100° C. with stirring, oxygen was introduced at 0.2 MPa, and the reaction was stirred at 500 rpm for 2 hours. After the reaction was completed, 1 g of triphenylphosphine was added to the reaction mixture, stirred at room temperature for 1 hour, and a sample was taken for gas chromatography analysis. The conversion rate of cyclononane was 23.2%, and the selectivity of ketone / alcohol was 93.8%.
[0054] Example 10 In a 100 mL polytetrafluoroethylene-lined autoclave, 21 g of cyclododecane and 0.01% of the supported material N of Example 5 were added, the mixture was heated to 120°C with stirring, and air was introduced at 1.15 MPa, and the mixture was stirred at 600 rpm for 2 hours. After the reaction was completed, 2 g of triphenylphosphine was added to the reaction mixture, and the mixture was stirred at room temperature for 1 hour, and a sample was taken for gas chromatography analysis. The cyclododecane conversion rate was 23.9%, and the ketone / alcohol selectivity was 94.9%.
Claims
1. A supported material, characterized in that A multi-level porous ZSM-5 molecular sieve loaded with vanadium compounds; wherein the molecular sieve carrier is a porous material modified with silicon and aluminum elements; the material is used for catalytic oxidation of cycloalkanes.
2. The supported material according to claim 1, characterized in that The vanadium compound comprises at least one compound selected from the following structures: 。 3. The supported material according to claim 1, characterized in that The pore size of the supported multi-level pore ZSM-5 molecular sieve is 2-20 nm; the loading amount of the vanadium compound in the supported material is 0.3-30%.
4. The supported material according to claim 1, characterized in that The particle size of the supported multi-level pore ZSM-5 molecular sieve is 100-500 nm, and the specific surface area is 300-800 m 2 / g, the silicon-aluminum atomic ratio is 20-500.
5. The supported material according to claim 1, characterized in that The preparation method of the carrier at least comprises: preparing the raw materials of silicon compound, aluminum compound, template agent and alcohol compound into dry gel; crystallizing the dry gel in an atmosphere containing water vapor under closed conditions to obtain a multi-level pore ZSM-5 molecular sieve.
6. The supported material according to claim 5, characterized in that Silicon substance: aluminum substance: template agent: alcohol compound = 1.01~1.15: 0.001~0.2: 0.01~0.2: 5~1000.
7. The supported material according to claim 5, characterized in that The mixed raw gel is placed at 10-50° C. and dried for not less than 24 hours to obtain the dry gel.
8. The supported material according to claim 5, characterized in that The crystallization time is 24 to 120 hours, and the crystallization temperature is 100° C. to 250° C.
9. The supported material according to claim 1, characterized in that The preparation method of the supported vanadium compound at least comprises: adding a carrier into a solution containing the vanadium compound, impregnating, drying and calcining to obtain the supported material.
10. The supported material according to claim 9, characterized in that The solid-liquid ratio of the impregnation is 1:2-15; the impregnation condition is: the stirring time is 8-24 hours; the roasting condition is: the roasting temperature is 200-800°C, and the roasting time is 1-8 hours.
11. According to claim 1, it is characterized in that: The oxidation reaction of the cycloalkane is completed under the catalysis of the supported material; the cycloalkane is a cycloalkane containing three or more carbon atoms, or a cycloalkane containing an alkyl substituent.
12. The method according to claim 11, characterized in that The type of the cycloalkane includes one of cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane and cyclododecane.
13. The method according to claim 11, characterized in that The amount of the supported material is 0.01 to 5% by weight based on the total weight of the reaction mixture.
14. The method according to claim 11, characterized in that The reaction pressure is 0.1-5 MPa, the reaction time is 1-600 minutes, and the reaction temperature is 0°C-200°C.
15. The method according to claim 11, characterized in that The oxidant is oxygen, air or any mixture thereof.
